2021
DOI: 10.21037/apm-20-1722
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for brain metastases in patients with non-small cell lung cancer: a meta-analysis of 43 studies

Abstract: Background: Lung cancer is a leading cause of cancer-related mortality worldwide. The purpose of our meta-analysis was to assess the risk factors for brain metastases (BM) in patients with non-small cell lung cancer (NSCLC).Methods: Multiple databases, including PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang, were systematically searched to recruit relevant studies investigating the risk factors for BM in NSCLC patients. The Newcastle-Ottawa Scale was used to eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…Lo et al also found that the assessment between reviewers and authors of the studies was very different (95). Interestingly, many studies that used the NOS cited this critical discussion instead of the original web-based link (96)(97)(98)(99), suggesting that researchers were using the problematic tool even though they were aware of the limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lo et al also found that the assessment between reviewers and authors of the studies was very different (95). Interestingly, many studies that used the NOS cited this critical discussion instead of the original web-based link (96)(97)(98)(99), suggesting that researchers were using the problematic tool even though they were aware of the limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Most current meta-analyses focused on one aspect, such as PCI or not in SCLC (101), ED-SCLC (82,90), and resected SCLC (102). Chen et al conducted a meta-analysis to identify risk factors for BM in NSCLC (97). Unfortunately, they only searched for observational studies instead of RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these factors align with the risk factors for brain metastases in NSCLC identified in prior research. 25 - 27 Nevertheless, prior studies have not established numerous predictive factors for NSCLC individuals with radiotherapy and inoperable brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“… 7 In addition, advances in treatments are leading to improved survival, thereby increasing the risk of relapse and/or metastasis to the brain. 8 Although recent clinical guidelines have recommended screening for brain metastases for stage II NSCLC and above, most brain metastases are detected after symptoms develop. 9 , 10 Surgical resection, stereotactic radiosurgery, and whole-brain radiation therapy are the primary treatment modalities.…”
Section: Introductionmentioning
confidence: 99%